Morphological and structural characterization of ceramic shell waste in the investment casting process in FASAB Sogamoso - Grandas-Rincón, Isnardo Antonio; Lara-González, Luis Ángel; Paredes-Roa, Ricardo Alfonso; Roa-Bohórquez, Karol Lizeth (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
The structural characteristics and the crystalline parameters of the waste material in the process of investment casting in the Military Industry (INDUMIL for its acronym in Spanish) Factory Santa Barbara are reported. By performing standard laboratory tests such as Optical Microscopy, Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD), particle size distribution, porosity and fractures present are identified. In addition, a qualitative and quantitative analysis of mineral phases is performed by determining the major phase and comparing the phases present in the original feedstock. Finally,based on information obtained, possible uses that may have the material under study are proposed.